Analysis of factors affecting the incidence of Pneumonia, length of stay in intensive care unit (ICU), and mortality in traumatic cervical spinal cord injury (tCSCI) patients after surgery - Wardhana, Wahyu Wiswa; Semedi, Bambang Pujo; Santosa, Dhania Anindita; Hamzah, Hamzah; Sumartono W, Christrijogo (Edelweiss Applied Science and Technology, 2024)
Spinal cord injury is a condition that has a catastrophic impact on the clinical, social, and economic well-being. It has a poor prognosis as it leads to neurologic impairments, as well as disruption of the diaphragmatic muscles. This condition is one of the risk factors associated with increased morbidity and mortality. All ICU patients who met the inclusion and exclusion criteria at Dr. Soetomo Hospital between January 2023 and January 2024 had their Electronic Medical Records (EMR) data used in this retrospective analytical study. The 38 patients in the sample were collected. All of the samples were male, and their average age was 45 years. Of these, 11 patients (29%), had 30-day mortality, while 21 patients (55%), had pneumonia. The majority of patients (n = 16; 42%) were classified as AIS A, and the lower cervical area was the most often affected lesion site (16; 42%). The most frequent mode of injury was falling from a height including 24 patients (63%). Fifteen patients (39%) underwent tracheotomies. Tracheostomy was the risk factor that affected the duration of ICU hospitalization (p<0.001) and the incidence of 30-day mortality (p=0.012; OR 7.61). The multivariate logistic regression analysis revealed no correlation between any of the covariates and the incidence of pneumonia. In other hand, tracheostomy is one factor that affects 30-day mortality and length of stay in the intensive care unit.